1997
DOI: 10.1097/00005053-199708000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Posttraumatic Stress Symptomatology in Police Officers: A Prospective Analysis

Abstract: This study examines internal and external risk factors for posttraumatic stress symptoms in 262 traumatized police officers. Results show that 7% of the entire sample had PTSD, as established by means of a structured interview; 34% had posttraumatic stress symptoms or subthreshold PTSD. Trauma severity was the only predictor of posttraumatic stress symptoms identified at both 3 and 12 months posttrauma. At 3 months posttrauma, symptomatology was further predicted by introversion, difficulty in expressing feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
230
5
7

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(253 citation statements)
references
References 44 publications
7
230
5
7
Order By: Relevance
“…Research has shown that the majority of persons in whom PTSD develops meet the criteria for the diagnosis of this disorder within the first three months after the traumatic event. 29 In our study, administering the surveys three to four months after the subjects had returned from deployment and at least six months after the heaviest combat operations was probably optimal for investigating the long-term risk of mental health problems associated with combat. We are continuing to examine this risk in repeated cross-sectional and longitudinal assessments involving the same units.…”
Section: Survey and Mental Health Outcomesmentioning
confidence: 95%
“…Research has shown that the majority of persons in whom PTSD develops meet the criteria for the diagnosis of this disorder within the first three months after the traumatic event. 29 In our study, administering the surveys three to four months after the subjects had returned from deployment and at least six months after the heaviest combat operations was probably optimal for investigating the long-term risk of mental health problems associated with combat. We are continuing to examine this risk in repeated cross-sectional and longitudinal assessments involving the same units.…”
Section: Survey and Mental Health Outcomesmentioning
confidence: 95%
“…3,5,17,21 Exposure to work-related stressors has been linked to stress reactions, most frequently to posttraumatic stress. 1,3,5,6,18,[22][23][24][25][26][27][28][29] Most research in this area has focused on the link between critical incident stress and posttraumatic stress symptomatology (PTSS). However, recent research has found preliminary evidence that chronic work stressors may significantly contribute to PTSS.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of current duty-related PTSD in police officers has been found to be 7–19% (Gersons, 1989): among 262 Dutch police officers interviewed at two weeks, three months, and 12 months after experiencing a critical incident, 34% suffered from PTSD or subsyndromal PTSD symptoms at some point during the study (Carlier et al, 1997). Moreover, over 30% of young, inexperienced police recruits developed stress-related symptoms after being exposed to a life-threatening situation (Maguen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, difficulties controlling automatic defensive responses may not only affect split-second decisions under acute threat, but also increase the risk for development and persistence of posttraumatic stress disorder (PTSD) symptoms (Kozlowska, Walker, McLean, & Carrive, 2015). PTSD symptoms are highly prevalent among police officers: it was estimated that over 34% of Dutch police officers experienced PTSD or subsyndromal PTSD symptoms within one year of experiencing a critical incident (Carlier, Lamberts, & Gersons, 1997). Revealing (neurobiological) mechanisms underlying the development and persistence of PTSD symptoms is an important research avenue (Lanius & Olff, 2017), potentially offering modifiable neurobiological targets for (early preventive) interventions for PTSD (Van Zuiden, Kavelaars, Geuze, Olff, & Heijnen, 2013).…”
Section: Introductionmentioning
confidence: 99%